2020
DOI: 10.1210/jendso/bvaa046.214
|View full text |Cite
|
Sign up to set email alerts
|

OR25-02 A Phase 3 Study of a Modified-Release Hydrocortisone in the Treatment of Congenital Adrenal Hyperplasia

Abstract: Background: Patients with congenital adrenal hyperplasia (CAH) due to classic 21-hydroxylase deficiency have poor health outcomes related to inadequate glucocorticoid (GC) replacement. We compared disease control of adults with classic CAH treated with a modified release hydrocortisone (MRHC), which replicates physiological diurnal cortisol secretion, versus standard GC therapy. Methods: 6 month, open label, study in 122 patients randomised either to treatment with MRHC (Chronocort®, Diurnal Ltd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A phase III trial including 122 patients with classic CAH revealed superior hormonal control during the early morning and early afternoon compared to patients receiving standard glucocorticoid therapy (338,385). 5).…”
Section: Treatment Of Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase III trial including 122 patients with classic CAH revealed superior hormonal control during the early morning and early afternoon compared to patients receiving standard glucocorticoid therapy (338,385). 5).…”
Section: Treatment Of Adultsmentioning
confidence: 99%
“…advantage over intermittent bolus administration because of lower variability and avoidance of regular troughs in plasma cortisol levels (385,410), but these two approaches have not been compared directly and clinical outcomes are likely similar. Stress dosing is indicated for pregnant women in active labor, similar to that used in major surgical stress (405).…”
Section: Continuous Intravenous Infusion Of Hydrocortisone Sodium Suc...mentioning
confidence: 99%
“…3) [55,56 ▪ ,57]. In the recently concluded phase 3 study ( n = 122) the 0700h-1500h 17-OHP profile was better with Chronocort compared to conventional glucocorticoid treatment ( P = 0.0251) [58 ▪▪ ].…”
Section: Modified Release Hydrocortisone Formulationsmentioning
confidence: 92%